Matrix metalloproteinases in exercise and obesity - Koh, Yunsuk; Jaoude, Jonathan (Vascular health and risk management, 2016)
Matrix metalloproteinases (MMPs) are zinc- and calcium-dependent endoproteinases that have the ability to break down extracellular matrix. The large range of MMPs' functions widens their spectrum of potential role as activators or inhibitors in tissue remodeling, cardiovascular diseases, and obesity. In particular, MMP-1, -2, and -9 may be associated with exercise and obesity. Thus, the current study reviewed the effects of different types of exercise (resistance and aerobic) on MMP-1, -2, and -9. Previous studies report that the response of MMP-2 and -9 to resistance exercise is dependent upon the length of exercise training, since long-term resistance exercise training increased both MMP-2 and -9, whereas acute bout of resistance exercise decreased these MMPs. Aerobic exercise produces an inconsistent result on MMPs, although some studies showed a decrease in MMP-1. Obesity is related to a relatively lower level of MMP-9, indicating that an exercise-induced increase in MMP-9 may positively influence obesity. A comprehensive understanding of the relationship between exercise, obesity, and MMPs does not exist yet. Future studies examining the acute and chronic responses of these MMPs using different subject models may provide a better understanding of the molecular mechanisms that are associated with exercise, obesity, and cardiovascular disease.